Fiber laser cutting of CFRP composites and process optimization through response surface methodology. Issue 14 (26th October 2017) - Rao, Shivdayal; Sethi, Abhijeet; Das, Alok Kumar; Mandal, Niladri; Kiran, P.; Ghosh, Rizul; Dixit, A. R.; Mandal, A.
ABSTRACT: In this experimental study, the effects of major laser process control parameters, such as the laser power, beam scanning speed and assisting gas flow rate, on cut surface integrity defined by the kerf width, taper percentage, and the extent of heat affected zone (HAZ) were investigated. Response surface methodology (RSM) along with central composite design (CCD) of the experiment was used to optimize the process parameters to get better-cut surface quality. The optimum values of process parameters corresponding to cut surface with minimum defects are laser power 260 W, cutting speed 4500 mm per min, and assistance gas flow rate 14.23 l/min and the corresponding kerf width, taper percentage, and the width of HAZ are found to be 163.7 µm, 5.75%, and 573.28 µm. The confirmation experiments have been conducted that provide favorable results with an error of 2.70%, 1.87%, and 0.36%, for kerf width, taper percentage, and width of HAZ, respectively.